Presence of Paragonimus species within secondary crustacean hosts in Bogotá, Colombia - Phillips, Gillian; Hudson, David M.; Chaparro-Gutiérrez, Jenny J. (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: Paragonimus spp. are trematode parasites that infect human populations worldwide. It is believed that infection rates within Asia reach five to ten percent of the total population. Three of the largest areas of possible infection are Asia, Central and South America as well as Africa, where the total population at risk is estimated to be 293 million people. Humans are infected via ingestion of raw or undercooked decapod crustaceans. Objective: To identify the presence of Paragonimus spp. in crabs from Bogotá, Colombia. Methods: The native crab Neostrengeria macropa and the aquatic invasive crayfish Procambarus clarkii in Bogotá, Colombia, were collected from local markets, pet stores and waterways and dissected to assess the presence of Paragonimus spp. Results: The native crab species, N. macropa (n=29) had an infection prevalence of 17.2%, while the invasive crayfish species, P. clarkii (n=22), had a prevalence of 36.4% combined from both field captured animals and purchased samples. Conclusion: Although the estimated prevalence is lower compared to previous studies in other cities of Colombia, Paragonimus represent a risk to human health. Several environmental factors may contribute to the difference in prevalence including collecting season, rainfall, temperature, altitude and the El Niño Southern Oscillation.